1948
DOI: 10.1103/physrev.73.679
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation Effects in Nuclear Magnetic Resonance Absorption

Abstract: The exchange of energy between a system of nuclear spins immersed in a strong magnetic field, and the heat reservoir consisting of the other degrees of freedom (the "lattice") of the substance containing the magnetic nuclei, serves to bring the spin system into equilibrium at a finite temperature. In this condition the system can absorb energy from an applied radiofrequency field. With the absorption of energy, however, the spin temperature tends to rise and the rate of absorption to decrease. Through this "sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

87
2,391
7
37

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 6,110 publications
(2,568 citation statements)
references
References 22 publications
87
2,391
7
37
Order By: Relevance
“…The influence of field strength can be ignored since all MRI measurements were performed at 1.5T. The results of a previous study (8) with theoretical models described in the literature (18,19). An increase in macromolecular content causes a reduction of the correlation times of the Gd-DOTA chelate or the water molecule, or both, leading to an increased rate of spin interaction.…”
Section: Discussionmentioning
confidence: 91%
“…The influence of field strength can be ignored since all MRI measurements were performed at 1.5T. The results of a previous study (8) with theoretical models described in the literature (18,19). An increase in macromolecular content causes a reduction of the correlation times of the Gd-DOTA chelate or the water molecule, or both, leading to an increased rate of spin interaction.…”
Section: Discussionmentioning
confidence: 91%
“…2,2,6,6-Tetramethylpiperidin-1-oxyl (tempo), 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl (tempol), 4-oxo-2,2,6,6-tetramethylpiperidin-1-oxyl (tempone) (Aldrich Chemical Co.); 3-carbamoyl-2,2,5,5-tetramethylpyrrolidin-1-oxyl (CPROXYL), 3-carbamoyl-2,2,5,5-tetramethylpyrrolin-1-oxyl (CTPO) (Eastman Kodak Co.); 15 N-tempone, tempone-d 16 , tempol-d 17 , and 15 N-tempol-d 17 (CDN Isotope) were used as received. TPHIO was prepared as reported in ref.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…However, there was ∼10% difference between derived τ values for tempol and tempol-d 17 in water:glycerol. The linewidths in the spectra of tempol are broader than for tempone and are substantially broader for tempol than for tempol-d 17 and 15 N-tempol-d 17 , which may introduce systematic errors in the calculation of τ. The average τ values obtained for tempol-d 17 and 15 N-tempol-d 17 were used in the analysis of the dependence of 1/T 1 on tumbling.…”
Section: Nitroxyl Tumbling Correlation Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…Albert et al [25] have assumed that the observed curves could be described by two superimposed BPP curves [31] and the effective relaxation rate is the sum of the relaxation rates due to the intramethyl and intermethyl contributions and hence can be written as…”
Section: Theorymentioning
confidence: 99%